Let a be greater than B and greater than 0, and the square of a + the square of b-6ab is equal to 0, then the square of a + the square of B-A is 0

Let a be greater than B and greater than 0, and the square of a + the square of b-6ab is equal to 0, then the square of a + the square of B-A is 0

From a ^ 2 + B ^ 2-6ab = 0, if a ^ 2 + B ^ 2 = 6ab, then (a + b) ^ 2 / (B-A) ^ 2 equals (a ^ 2 + B ^ 2 + 2Ab) / (b ^ 2 + A ^ 2-2ab) equals (6ab + 2Ab) / (6ab-2ab) = 8ab / 4AB = 2
Hope to help you, I wish you progress in learning